Occurrence and distribution of perfluoroalkyl substances (PFASs) in surface water and bottom water of the Shuangtaizi Estuary, China. (September 2016) - Shao, Mihua; Ding, Guanghui; Zhang, Jing; Wei, Lie; Xue, Huanhuan; Zhang, Nannan; Li, Yang; Chen, Guanqun; Sun, Yeqing
Abstract: Perfluoroalkyl substances (PFASs) have been recognized as emerging environmental pollutants. However, there is limited information on the contamination level and spatial distribution of PFASs in the Shuangtaizi Estuary, where the Shuangtaizi Hekou Nature Reserve is located. In the present study, the contamination level and spatial distribution of PFASs in surface water (approximately 0.5 m below the surface) and bottom water (about 0.5 m above the bottom) of the Shuangtaizi Estuary were investigated. The data indicated that the Shuangtaizi Estuary was commonly contaminated by PFASs. The total concentration of PFASs in surface and bottom water of the Shuangtaizi Estuary ranged from 66.2 to 185 ng L −1 and from 44.8 to 209 ng L −1, respectively. The predominant PFASs were perfluorobutanoic acid (PFBA), perfluoropentanoic acid, perfluorooctanoic acid, perfluorohexanoic acid and perfluorobutane sulfonate (PFBS). In general, PFAS concentrations in surface water samples were lower than those in bottom water samples. The spatial distribution of PFASs in the Shuangtaizi Estuary was mainly affected by particular landform, tide and residual currents in Liaodong Bay. The total mass flux of 15 PFASs from the Shuangtaizi River to Liaodong Bay was estimated to be 352 kg year −1, which was lower than the total flux from the Daling River and the Daliao River. As short-chain PFASs, such as PFBS and PFBA, have been the prevalent compounds in some places and are continuously produced and used, long-term monitoring and effective pollution controls are suggested. Graphical abstract: Highlights: The Shuangtaizi Estuary was commonly contaminated by PFASs. The predominant PFASs were PFBA, PFPeA, PFOA, PFHxA and PFBS. PFASs in surface water were generally lower than those in bottom water. Particular landform, tide and residual currents affected the distribution of PFASs. The mass flux of PFASs from the Shuangtaizi River to Liaodong Bay was 352 kg year −1 . Abstract : PFASs in surface water were generally lower than those in bottom water, and particular landform, tide and residual currents affected the distribution of PFASs.